A Portable LIFT Printer to Enable the Fast On‐Site Optimization of Inks Toward Special Customer Needs - Stefan Lux; Chaoyu Wu; Christina Salazar; Julian Crespo; Angélica Pérez; Claudio Fernández Acevedo; Dario Mager; Mareen Stahlberger; Daniela Mattes; Laura Weber; Jannik Schlindwein; Clarine Gedigk; et al. (Nano Select)
ABSTRACT Laser‐induced forward transfer (LIFT) printing uniquely enables localized deposition of nanoparticle pastes onto target substrates. The extent of its versatility hinges upon the availability of nanoparticle inks that align with the capabilities of the printing device. Given the inherent distinctions among various devices attributed to differences in laser types (continuous‐wave or pulsed), laser energy profiles, and adaptable wavelengths, ink formulation and the LIFT printing processes are frequently disjointed, which results in a lengthy optimization cycle. Significantly expedited optimization cycles could be achieved if LIFT performance of an ink could be tested on‐site of the ink developer. This localization empowers ink developers to tailor inks precisely to specific usage scenarios by promptly adjusting parameters such as particle size, viscosity, and surface properties. This paper presents a dedicated LIFT device that focuses on fine‐tuning ink characteristics and provides insights into the construction to allow other interested researchers to build similar low‐cost, user‐friendly setups.